"The multiplicity of syntactic aspects and their effect on directing meaning in the kitab of alshaer by Abu Ali Al- Farsi"(d.377 AH) - Yaqoub Hilal, Wisam (Journal of College of Education, 2021)
The relationship between syntax and meaning is a close relationship as the validity of one is based on the integrity of the other, and the multiplicity of the expression leads to a multiplicity of meaning and vice versa, as the meaning in many places leads to directing the expression to a face with which the meaning is correct or elevated. Due to the importance of this relationship, many scholars, in the past and present, have been studying it and demonstrating its importance in guiding texts, especially the texts and readings of the Holy Qur’an. From the multiplicity of expression and meaning and the impact of each on the other. Poetry had a share of these studies, and it appeared in the past in several books, including books of grammar when they dealt with poetic evidence, including books dealing with this topic, especially what he called the verses of meanings, and “The kitab of alshaer or Explanation of Verses that Form the Syntax” by “Abu Ali Al-Farsi” from the books that I studied the verses of the meanings, as its author has been analyzing many poetic verses and directing the parsing and meaning in them, and part of these verses had multiple directions of parsing in them, and it was followed in many positions of the direction of meaning. And study it.